Lift becoming a positive force in any situation - Quinn, Ryan W. (BK business book., 2009)
Bestselling author Robert E. Quinn and his son Ryan present a combination of science and stories to illustrate the tools for achieving a transformative new vision, a new voice, and a new and positive perspective in any situation.